The Importance Of Involvement: Examining The Impact Of Somethinc’s Instagram Page On Future Purchase Intention - Hidayat, Anas; Windria Khoirunnisaa, Ulfah (Devotion : Journal of Research and Community Service, 2022)
Effective online marketing today is through social media, because the users are many and wide, therefore this research examines the marketing done on Instagram. The purpose of this study is to examine the effect of Brand Familiarity, Involvement on Brand’s Social Media, Attitude Towards Brand’s Social Media, and Future Purchase Intention towards Somethinc’s Instagram Page. This research uses purposive random sampling method. The data collection was done by distributing online questionnaires via google form with a total sample size of 250 people. AMOS 22.0 software was used to analyze the data. The result show that 1) Involvement on brand’s social media positively influences attitude towards the brand’s social media, 2) Involvement on a brand’s social media positively influences future purchase intention, 3) Attitude towards a brand’s social media positively influences future purchase intention, 4) Brand familiarity positively influences consumer involvement on brand’s social media.